2016
DOI: 10.1186/s40064-016-3181-6
|View full text |Cite
|
Sign up to set email alerts
|

Speech-generating devices: effectiveness of interface design—a comparative study of autism spectrum disorders

Abstract: Background We analyzed the efficacy of the interface design of speech generating devices on three non-verbal adolescents with autism spectrum disorder (ASD), in hopes of improving their on-campus communication and cognitive disability. The intervention program was created based on their social and communication needs in school. Two operating interfaces were designed and compared: the Hierarchical Relating Menu and the Pie Abbreviation-Expansion Menu.Methods The experiment used the ABCACB multiple-treatment rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Os usuários demostraram interesse e não apresentaram grandes dificuldades na utilização [28,29]. Para os outros dois, foram desenvolvidos protótipos de perspectivas diferentes para determinar a melhor proposta de acordo com as necessidades do usuário [30,31].…”
Section: 24unclassified
“…Os usuários demostraram interesse e não apresentaram grandes dificuldades na utilização [28,29]. Para os outros dois, foram desenvolvidos protótipos de perspectivas diferentes para determinar a melhor proposta de acordo com as necessidades do usuário [30,31].…”
Section: 24unclassified
“…The effectiveness of the picture-based systems on the speech development of the children with disorders, in particular children with Autistic spectrum disorders, has been studied and analyzed in [29]. The article by Chen et al has shown that both types, the speech-generating devices and the picture-based systems, are equally effective and can be applied in clinical practice.…”
Section: ) All Mobile Apps Have a Picture-based Interfacementioning
confidence: 99%